2016
DOI: 10.1261/rna.057547.116
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function relationships of archaeal Cbf5 during in vivo RNA-guided pseudouridylation

Abstract: In Eukarya and Archaea, in addition to protein-only pseudouridine (Ψ) synthases, complexes containing one guide RNA and four proteins can also produce Ψ. Cbf5 protein is the Ψ synthase in the complex. Previously, we showed that Ψ's at positions 1940, 1942, and 2605 of Haloferax volcanii 23S rRNA are absent in a cbf5-deleted strain, and a plasmid-borne copy of cbf5 can rescue the synthesis of these Ψ's. Based on published reports of the structure of archaeal Cbf5 complexed with other proteins and RNAs, we iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 92 publications
2
10
0
Order By: Relevance
“…tRNAs were separated from other RNAs by PAGE on 6% denaturing gel and eluted. The presence of Ψ in the tRNA was determined by primer extension following CMCT treatment, as described previously (Majumder et al 2016). Briefly, 20 µg tRNA enriched total RNA (6 µg tRNA and 14 µg total RNA) was treated with CMCT for 20 min at 37°C, while an untreated sample was simply incubated at 37°C for 20 min as control.…”
Section: Determination Of the Presence Of ψ At Specific Positions In mentioning
confidence: 99%
“…tRNAs were separated from other RNAs by PAGE on 6% denaturing gel and eluted. The presence of Ψ in the tRNA was determined by primer extension following CMCT treatment, as described previously (Majumder et al 2016). Briefly, 20 µg tRNA enriched total RNA (6 µg tRNA and 14 µg total RNA) was treated with CMCT for 20 min at 37°C, while an untreated sample was simply incubated at 37°C for 20 min as control.…”
Section: Determination Of the Presence Of ψ At Specific Positions In mentioning
confidence: 99%
“…The sequential nature of SL2-guided-modifications could be one of the several reasons for this difference. (vi) Our previous in vivo study (Majumder et al 2016) showed that certain mutations of Cbf5 produce Ψ2605 and Ψ1940, but not Ψ1942 (P110A/R112A and L52A in Table 2), suggesting that in vivo these mutants can catalyze the first (Ψ1940) but not the second (Ψ1942) reaction. (P110 and R112 are in the thumb loop of Cbf5 and L52 precedes catalytic D53.)…”
Section: Discussionmentioning
confidence: 91%
“…In a previous in vivo study, we observed that certain mutations of H. volcanii Cbf5 either eliminated or reduced the modification of one or more of the three U's, U1940, U1942, and U2605 (Majumder et al 2016). We reasoned that partial conversion of U to Ψ in vivo indicated a slower rate of Ψ formation.…”
Section: Certain Mutants Of Cbf5 Affect Modification More Under Atypical Guide-target Interactions Than Under Typical Onesmentioning
confidence: 87%
See 2 more Smart Citations